2023
DOI: 10.1038/s41598-023-28601-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors driving the abundance of Philaenus spumarius in mesomediterranean habitats of Corsica (France)

Abstract: Philaenus spumarius (Ps) is considered the main insect vector of the bacterium Xylella fastidiosa (Xf) in Europe. As such, it is a key actor of the Xf pathosystem on which surveillance and management strategies could be implemented. Although research effort has increased in the past years, the ecological factors shaping Ps abundance and distribution across landscapes are still poorly known in most regions of Europe. We selected 64 plots of 500m2 in Corsican semi-natural habitats in which we sampled nymphs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Potential counter measures include: 1) local elimination or population reduction of P . spumarius by management of agriculturally adjacent host plants [ 2 , 106 , 212 , 237 ], 2) reduction or elimination of plant sources of Xylella fastidiosa infection [ 21 ], and 3) reduction of target plant susceptibility, through selection of cultivars with genetic resistance or other measures that reduce plant vulnerability to transmission and/or infection [ 2 , 21 , 241 , 242 ]. In turn, P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential counter measures include: 1) local elimination or population reduction of P . spumarius by management of agriculturally adjacent host plants [ 2 , 106 , 212 , 237 ], 2) reduction or elimination of plant sources of Xylella fastidiosa infection [ 21 ], and 3) reduction of target plant susceptibility, through selection of cultivars with genetic resistance or other measures that reduce plant vulnerability to transmission and/or infection [ 2 , 21 , 241 , 242 ]. In turn, P .…”
Section: Discussionmentioning
confidence: 99%
“…Our results substantiate Ossiannilsson's undocumented 1981 assertion that P. spumarius has more than 1000 hosts [211], an informed guess that had become embedded in the literature (cf. [4,54,212]), despite a lack of supporting evidence. A 1977 statement by Halkka & Mikkola [213] that there are "nearly 4000 recorded food-plant species" is clearly a typographical error.…”
Section: Why Is P Spumarius So Polyphagous?mentioning
confidence: 99%
“…Chartois et al. (2023) found a strong association between nymph and adult P. spumarius and the rockrose shrub Cistus monspeliensis in Corsica, suggesting that retained chemical signals in generations of P. spumarius may be influencing its preference to this host, which could also provide a possible explanation to high abundance in heathland habitats in Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…Chatois et al (2003), highlighted a positive relationship between Ps abundance and the density of Cistus monspeliensis. They also found larger populations of Ps in cooler and moister plots [58]. Lester et al observed that among the various botanical families, those with the highest occurrence of host plants harboring Philaenus spumarius nymphs included Lamiaceae (10%), Rosaceae (10%), Onagraceae (9%), and Poaceae (9%).…”
Section: Hosts Observedmentioning
confidence: 97%
“…In southern Italy, for instance, the summer migration of adult insects from ground-level vegetation to the canopy has been noted in conjunction with the desiccation of herbaceous plants [49,58]. In particular, adults of Philaenus spumarius were observed from May to August in the vicinity of olive orchards, and on groves of Quercus ilex, Quercus crenata, Pistacia lentiscus, P. terebinthus, Hedera helix and Myrtus communis [49,59].…”
Section: Hosts Observedmentioning
confidence: 99%